Peran Sektor Pertanian Terhadap Perekonomian Kabupaten Kepulauan Talaud - Batunan, Aprince Katoci; Porajow, Oktavianus; Katiandagho, Theodora Maulina (AGRI-SOSIOEKONOMI, 2023)
This research aims to determine the role of the agricultural sector in the economy of the Talaud Islands Regency and its development in the 5 year period from 2017 to 2021 and also to determine whether the agricultural sector is a base or non-base sector. This research was conducted for 3 months starting from November 2022 to January 2023. The data used is secondary data. This secondary data was obtained from related agencies, namely BPS North Sulawesi Province and BPS Talaud Islands Regency. The data is then analyzed using contribution, growth and LQ formulas. The research results show that the agricultural sector has a very important role in the economy of the Talaud Islands Regency. The contribution of the agricultural sector ranks first highest, the average GDP growth in the agricultural sector tends to increase, and the agricultural sector is the base sector.